What Kind of Responsibility Do We Have for Fighting Injustice? A Moral-Theoretic Perspective on the Social Connections Model. Issue 2 (3rd April 2019) - Zheng, Robin
ABSTRACT: Iris Marion Young's influential Social Connections Model (SCM) of responsibility offers a compelling approach to theorizing structural injustice. However, the precise nature of the kind of responsibility modelled by the SCM, along with its relationship to the liability model, has remained unclear. I offer a reading of Young that takes the difference between the liability model and the SCM to be an instance of a more longstanding distinction in the literature on moral responsibility: attributability vs. accountability. I show that interpreting the SCM as a conception of accountability resolves a number of objections, while also highlighting the SCM's distinctive stance on the relationship between ethics and politics.